A Case of Undetected Neuroborreliosis in a 75-Year-Old Chinese Male - Jenny Lamichhane; Rohail Haider; Michael Bekkerman; Sean Tilford; Shireen Hijaz; Bikash Bhattarai; Rajanish Bobde (Case Reports in Infectious Diseases)
Lyme disease is a multisystem infection caused by the spirochete Borrelia burgdorferi sensu stricto that manifests with characteristic symptoms in patients. Patients are identified based on their clinical symptoms and then diagnosed through enzyme-linked immunosorbent assay (ELISA), Western blot, and blood culture techniques. Here, we present the case of a 75-year-old, Northeast suburban resident complaining of unstable gait, high fevers, malaise, myalgia, and confusion. This patient’s symptoms were nonspecific, and his lab titers and blood cultures were repeatedly negative during his stay. It was only late in the course of his treatment that blood titers and cerebrospinal fluid analysis were positive for Lyme IgG and IgM. He was treated with intravenous doxycycline and prescribed oral doxycycline on discharge, resulting in a full recovery. We express the need for physicians to consider Lyme disease in endemic patients presenting with nonspecific systemic signs.